Edukasi Smart Citizens Melawan Hoaks: Mengenal Zat Kimia Aman Dan Berbahaya Dalam Makanan Melalui Aplikasi “Chemical Quest” Di SMA Negeri 1 Percut Sei Tuan - Abdinur Batubara; Ramsul Nababan; Nurhalimah Br Ginting; Hary Fitra Ramadani (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Hoaxes about chemicals in food have spread in society and have caused misinformation that has a negative impact on food safety. Many natural and added chemicals in food are considered dangerous without strong scientific evidence. This community service aims to educate students at SMA Negeri 1 Percut Sei Tuan about the safety and dangers of chemicals in food using the educational application "Chemical Quest". This application integrates an interactive game approach that makes it easier for students to understand facts and myths related to chemicals in food. Service methods include initial presentations, application use, and evaluation through pre-tests and post-tests. The results show an increase in students' understanding in detecting hoaxes and their ability to think critically regarding food safety issues. This article also discusses the effectiveness of gamification in increasing scientific literacy among students.